Graphene‐Based Supercapacitors: Direct Semiconductor Laser Writing of Few‐Layer Graphene Polyhedra Networks for Flexible Solid‐State Supercapacitor (Adv. Electron. Mater. 7/2018). (9th July 2018) - Liu, Chunlin; Liang, Hongwei; Wu, Dun; Lu, Xiangyu; Wang, Qiang
Abstract : In article number1800092, Qiang Wang and co‐workers apply semiconductor laser writing on polyimide sheets to assemble a carbonaceous membrane packed with nanopolyhedra. The resulting solid‐state supercapacitor, using a Li‐containing gel electrolyte, exhibits a substantially enhanced specific capacitance due to combining Faradaic intercalation and non‐Faradaic absorption of Li‐ions.